A Supervision of Solidarity - Reynolds, Vikki (Canadian Journal of Counselling and Psychotherapy, 2010)
This article illustrates an approach to therapeutic supervision informed by a philosophy of solidarity and social justice activism. Called a Supervision of Solidarity, this approach addresses the particular challenges in the supervision of therapists who work alongside clients who are subjected to social injustice and extreme marginalization. It asks, “How can we as therapeutic supervisors support therapists to do this difficult work in the margins in ways that are in accord with our collective ethics? How can we (both therapists and their supervisors) experience sustainability and transformation collectively across time?” The article provides an example of this form of supervision, highlighting key aspects of the work.